Evaluasi Karaker Gotong Royong Pada Siswa Taman Kanak-Kanak (TK): Sebuah Studi Awal - Devina, Feri; Nurdin, Encep Syarief; Ruyadi, Yadi; Kosasih, Aceng (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2025)
The main issue in this research is the lack of understanding and deep habituation of essential character values. The purpose of this study was to evaluate the character of mutual cooperation in kindergarten students in Bandung City, Indonesia. The methodology of this research uses quantitative methods and quasi-experimental techniques. The research design adopted is the non-equivalent pretest-posttest Post-test Control Group Design. Data were collected using a Likert scale questionnaire given to the students' parents. This questionnaire measures the components of mutual cooperation. A total of 26 respondents from School A and 18 respondents from School B participated in this study. The analysis results show that the character of mutual cooperation is already possessed by students in both schools. The average score for mutual cooperation is 1.77 (SD = 1.107) in School A and 1.50 (SD = 0.786) in School B. However, these values need to be improved. This research recommends the use of the traditional Papancakan game to strengthen the character of mutual cooperation. The integration of local cultural wisdom into the early childhood education curriculum is very important for the development of children's character.